Transferring Information about Human Papillomavirus and Vaccine from Student to Family - Gulbol, Seda; Kochan, Zarife; Karaca Saydam, Birsen (Journal of Liaquat University of Medical & Health Sciences, 2025)
OBJECTIVE: Determining and increasing the awareness of midwifery students and their families about Human Papilloma Virus (HPV) and vaccines (HPVV). METHODOLOGY: The study is of descriptive type. The study was conducted at Ege University Faculty of Health Sciences (EUFHS). The population consisted of all students studying in the Department of Midwifery at EUFHS and their families, and the sample consisted of voluntary participants. Data were collected between September and November 2023. Trainings were conducted face-to-face in faculty classrooms, brochures were distributed, and the questionnaire and Human Papillomavirus Knowledge Scale (HPV-KS) were collected online (Google Forms). The questionnaire and scale were administered twice to the students (before and after the training) and once to their families. Students were asked to educate at least one family member with the brochure. 303 pre-training (PR-T), 179 post-training (PS-T) students and 105 family members participated. Data were analyzed using a t-test, Bonferroni test, and Analysis of Variance in the SPSS 25, and significance was evaluated at a 95% confidence interval. RESULTS: The mean HPV-KS scores of the students were calculated as PR-T 10.95±5.52 (min: 0, max: 21.0), PS-T 15.39±2.70 (min: 9.0, max: 27.0), and the difference between them was found to be statistically significant (t = 11.806; p < 0.05). It was determined that 71.3% of the students who received training provided education to their families about 'HPV and HPVV. CONCLUSION: As a result of the research, the students' knowledge level increased, and accurate and reliable information was relayed from them to their families.